2008
DOI: 10.1074/jbc.m709936200
|View full text |Cite
|
Sign up to set email alerts
|

A New Small Molecule Inhibitor of Estrogen Receptor α Binding to Estrogen Response Elements Blocks Estrogen-dependent Growth of Cancer Cells

Abstract: Estrogen receptor ␣ (ER␣)3 is a member of the steroid/nuclear receptor family of transcription regulators and mediates cell growth and metastasis and resistance to apoptosis and immunosurveillance (1-5). ER␣ is activated by binding of 17␤-estradiol (E 2 ), or by the epidermal growth factor-activated extracellular signal-regulated kinase pathway and other signal transduction pathways (6). ER␣-mediated gene transcription contributes to the development and spread of breast, uterine, and liver cancer (5,7,8). A ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 59 publications
1
52
0
Order By: Relevance
“…Studies have shown that prevention of ER binding to ERE sequences of responsive genes by exogenously introduced ERE decoys (21) or electrophilic agents that disrupt zinc-fingers of ERα (22)(23)(24) represses E2-mediated growth of ERpositive breast cancer cells. Complementing this, we recently reported that genomic responses from the ERE-dependent pathway mediated by E2-ER are required to suppress the growth of ER-negative cells as well (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that prevention of ER binding to ERE sequences of responsive genes by exogenously introduced ERE decoys (21) or electrophilic agents that disrupt zinc-fingers of ERα (22)(23)(24) represses E2-mediated growth of ERpositive breast cancer cells. Complementing this, we recently reported that genomic responses from the ERE-dependent pathway mediated by E2-ER are required to suppress the growth of ER-negative cells as well (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Since ER plays a pivotal role in both the initial response and subsequent resistance to antiestrogenic compounds, additional therapeutic benefits could be achieved by preventing ER synthesis or function. Repression of ER synthesis by inhibitory RNA technologies (43) or interference with endogenous ER functions by future generations of antiestrogenic compounds (44) or ERspecific electrophilic agents (22)(23)(24) could constitute strategies for the treatment of acquired endocrine-resistant breast cancers. Since these approaches target ER, however, circumvention of ER-dependent events by growth signaling pathways could lead to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…To explore in further detail whether direct binding of ER␣ to the EREs in the distal and proximal ER binding sites is necessary for chromosome interaction, we specifically blocked ER␣ from binding to DNA with TPBM, a newly identified small molecular inhibitor that binds to the DNA binding domain of ER␣ (18). As shown in Fig.…”
Section: Er␣ Directly Mediates Long Distance Chromatin Interactions Amentioning
confidence: 99%
“…An effective small molecule inhibitor of AR should exhibit high potency and specificity. Our studies show that CPIC inhibits AR transcriptional activity, with little or no effect on GR or ER␣ under the same conditions where other small molecules robustly inhibited ER␣ and GR (26,48). CPIC effectively inhib-FIGURE 10.…”
Section: Discussionmentioning
confidence: 99%